Measuring effectiveness and efficiencies of training and development practices and policies of First Securities Islami Bank Limited - Ahmed, Syed Salman (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.